Дослідження морфофункціональних особливостей розвитку експериментальних металонефропатій = The study of morphofunctional features of the development of experimental metallonephropathy - Gozhenko, A. I.; Lugovskoy, S. P.; Samokhina, N. A. (Journal of Education, Health and Sport, 2016)
Gozhenko A. I., Lugovskoy S. P., Samokhina N. A. Дослідження морфофункціональних особливостей розвитку експериментальних металонефропатій = The study of morphofunctional features of the development of experimental metallonephropathy. Journal of Education, Health and Sport. 2016;6(4):287-296. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50201 http://ojs.ukw.edu.pl/index.php/johs/article/view/3473 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.03.2016. Revised 17.04.2016. Accepted: 17.04.2016. ДОСЛІДЖЕННЯ МОРФОФУНКЦІОНАЛЬНИХ ОСОБЛИВОСТЕЙ РОЗВИТКУ ЕКСПЕРИМЕНТАЛЬНИХ МЕТАЛОНЕФРОПАТІЙ А. І. Гоженко, С. П. Луговський, Н. А. Самохіна Державне підприємство «Український науково-дослідний інститут медицини транспорту МОЗ України», м. Одеса, Украина Резюме Проведені експериментальні дослідження щодо тривалого впливу солей кадмію, ртуті, свинцю в дозі 1/50 від DL50 на нирки показали, що важливим аспектом їх дії є зміна показників азотистого обміну, яка проявлялась підвищеним вмістом креатиніну, сечовини та сечової кислоти в сироватці крові, а також високим вмістом білку в сечі. Характерною ознакою ураження нирок є зниження швидкості клубочкової фільтрації, яка визначалась при дії всіх трьох досліджуваних нефротоксикантів: при дії Cd – зниження на 23,6 %, при дії Pb – на 22,1 %, при дії Hg – 28,9 %. Морфологічні дослідження дозволили встановити нові факти, щодо морфологічної характеристики токсичної дії неорганічних сполук Cd, Hg, Pb, які полягають у здатності металів викликати цитопатичну дію на окремі клітини структурних елементів нефрону. Провідним механізмом розвитку експериментальних металонефропатій є ураження епітелію проксимальних канальців нирок, яке зумовлено вибірковим порушенням клітинних мембран, мітохондрій і лізосом епітелію проксимальних канальців нефрону. Ключові слова: важкі метали, нирки, металонефропатії, креатинін, сечовина, білок, швидкість клубочкової фільтрації, гістологічне дослідження нирок, канальцевий апарат, епітеліоцити. THE STUDY OF MORPHOFUNCTIONAL FEATURES OF THE DEVELOPMENT OF EXPERIMENTAL METALLONEPHROPATHY A. I. Gozhenko, S. P. Lugovskoy, N. A. Samokhina Ukrainian Scientific and Research Institute of Transport Medicine, Odessa Summary Eexperimental studies of prolonged exposure of cadmium salts, mercury, lead in the dose of from 1/50 DL50 on the kidney have shown that an important aspect of their actions is the change of indicators of nitrogen metabolism, which was manifested by increased creatinine, urea and uric acid in serum and high urine protein excretion. A characteristic feature of renal disease is the decline in glomerular filtration rate, which was defined when all three of the studied nephrotoxicants: under the Cd decrease by 23,6 %, under the action of Pb - 22,1 %, under the action of Hg – 28,9 %. Morphological studies revealed new facts concerning the morphological characteristics of toxic action of inorganic compounds of Cd, Hg, Pb, which lies in the ability of metals to cause cytopathic effect on individual cells of the structural elements of the nephron. The main mechanism for the development of experimental metallonephropathy is the damage to the epithelium of the proximal tubules of the kidneys, due to a selective disturbance of cellular membranes, mitochondria and lysosomes in the epithelium of the proximal tubules of the nephron. Key words: heavy metals, kidneys, metallonephropathy, creatinine, urea, protein, glomerular filtration rate, and histological examination of the kidneys, tubular apparatus, the epithelial cells. ИССЛЕДОВАНИЕ МОРФОФУНКЦИОНАЛЬНЫХ ОСОБЕННОСТЕЙ РАЗВИТИЯ ЭКСПЕРИМЕНТАЛЬНЫХ МЕТАЛЛОНЕФРОПАТИЙ А. И. Гоженко, С. П. Луговской, Н. А. Самохина Украинский НДИ медицины транспорта, г.Одесса Резюме Проведенные экспериментальные исследования длительного воздействия солей кадмия, ртути, свинца в дозе 1/50 DL50 на почки показали, что важным аспектом их действия является изменение показателей азотистого обмена, которое проявлялось повышенным содержанием креатинина, мочевины и мочевой кислоты в сыворотке крови, а также высоким содержанием белка в моче. Характерным признаком поражения почек является снижение скорости клубочковой фильтрации, которая определялась при действии всех трех исследуемых нефротоксикантов: при действии Cd – снижение на 23,6 %, при действии Pb – на 22,1 %, при действии Hg – 28,9 %. Морфологические исследования позволили установить новые факты, относительно морфологической характеристики токсического действия неорганических соединений Cd, Hg, Pb, которые заключаются в способности металлов вызывать цитопатическое действие на отдельные клетки структурных элементов нефрона. Ведущим механизмом развития экспериментальных металонефропатий является поражение эпителия проксимальных канальцев почек, которое обусловлено выборочным нарушением клеточных мембран, митохондрий и лизосом эпителия проксимальных канальцев нефрона. Ключевые слова: тяжелые металлы, почки, металлонефропатии, креатинин, мочевина, белок, скорость клубочковой фильтрации, гистологическое исследование почек, канальцевый аппарат, эпителиоциты.